Clinical phenotypic and genotypic characterization of NPRL3-related epilepsy - Zhang, Hongwei; Deng, Jie; Wang, Xiaohui; Chen, Chunhong; Chen, Shuhua; Dai, Lifang; Fang, Fang (Frontiers in Neurology, 2023)
Background: As one of the assembly factors of GATOR1 protein complex in the mechanism of rapamycin (mTOR) pathway, NPRL3 plays an important role in the pathogenesis of epilepsy. However, the correlation of genotype-clinical phenotype in patients with NPRL3-related epilepsy has not been clarified. Methods: Eleven Chinese children with NPRL3-related epilepsy were identified through whole-exome sequencing (WES). The clinical presentation, laboratory data, brain imaging findings, genetic results, and treatment methods were collected. All previously reported cases with NPRL3 -related epilepsy were collected and reviewed using a PubMed search. Results: Among the eleven children, eight have not been reported, two of whom presented infantile spasms (IS) as a new phenotype of NPRL3-related epilepsy. WES revealed five were frameshift mutations, three were nonsense mutations, two were missense mutations, and one was exon deletion. Bioinformatics analysis revealed that two missense mutation sites were highly conserved, and the c.400G>A mutation site of the NPRL3 gene caused the alteration of protein structure. To date, eighty-eight patients have been reported with NPRL3 defects, including our eleven cases. The most common presentations were sleep-related hyper-motor epilepsy (SHE), frontal lobe epilepsy (FLE), and temporal lobe epilepsy (TLE). A majority of patients presented normal neuroimaging results (70%), and focal cortical dysplasia was the most common neuroimaging abnormality (62.5%). Among these mutations, loss of function was the most common genetic variation (75%). The monotherapy of sodium channel blockers was effective for 73% of patients with NPRL3-related epilepsy. Surgery was effective for 75% of children with neuroimaging abnormalities. Two cases unresponsive to surgery or anti-seizure medications were treated effectively by ketogenic diets (KD). One case was treated effectively by rapamycin at early stage of epilepsy. Conclusion: NPRL3-related epilepsy has high clinical and genetic heterogeneity. SHE and FLE are the most common clinical presentations, further IS is a new phenotype of NPRL3-related epilepsy, while the variants c.275G>A, c.745G>A, and c.1270C>T may be most common NPRL3 gene mutations. Sodium channel blockers, surgery, KD, and rapamycin may be the potential treatments for these patients. Our study expanded the clinical and genetic spectrum of NPRL3-related epilepsy, and provided important information for the precise treatment of patients.